2003
DOI: 10.1080/ejc.8.4.197.202
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral versus vaginal misoprostol on cervical dilatation in first-trimester abortion: a double-blind, randomized study

Abstract: Different methods of misoprostol administration may not be equivalent in terms of efficacy and side-effects. Therefore, we decided to extend the study to include more patients so as to achieve statistically significant results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although a variety of medical abortion methods have been introduced during the past decade [12][13][14][15] , surgical methods have a considerable popularity. A data analysis of five randomized studies of any surgical abortion method compared with any medical abortion method in the first trimester has suggested that medical methods seem to be less effective and more painful compared to surgical first-trimester abortion 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a variety of medical abortion methods have been introduced during the past decade [12][13][14][15] , surgical methods have a considerable popularity. A data analysis of five randomized studies of any surgical abortion method compared with any medical abortion method in the first trimester has suggested that medical methods seem to be less effective and more painful compared to surgical first-trimester abortion 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vaginal administration was found to be more effective than oral administration later in the first trimester and in multiparous women [102,148]. However, other studies have shown no difference between vaginal and oral administration [90,92,103,149]. Such studies have shown that 400 mcg of oral misoprostol produced equivalent dilatation at 3 h to 400-mcg vaginal dosing, all with similar side effects.…”
Section: Comparisonsmentioning
confidence: 97%
“…The degree to which anything is soluble in water. In reality, there is a scarcity of data on the human vaginal permeability of drugs with various physicochemical properties; far further research is required on the effects of physicochemical drug parameters on vaginal absorption 38 .…”
Section: Physicochemical Properties O Drugsmentioning
confidence: 99%